Проблеми та перешкоди на шляху забезпечення провадження алокаційного управління розвитком промислового потенціалу України - Чупріна, М. О.; Chuprina, M. (КНТУ, 2015)
Обґрунтовано, що розвиток промислового потенціалу є об’єктивною основою задля генерування ознак надійності функціонування національної економічної системи. Визначено, що реалізації концепції алокаційного управління розвитком промислового потенціалу України потребує активізації інвестиційної діяльності, як визначального фактора прогресивних структурних зрушень та передумови для прискорень процесів провадження прогресивної трансформації у структурі промислового виробництва та оновлення виробничого потенціалу. Здійснено уточнення і деталізація проблем та перешкод на шляху формування і застосування алокаційного управління розвитком промислового потенціалу України. The purpose of the article is accurate and detail definition of challenges and obstacles on the way to the formation and application of allocative management for development of industrial potential of Ukraine. It has been proved that the development of industrial potential is an objective basis for generating signs of reliability of the national economic system. It has been determined that the implementation of the concept of allocative management for development of industrial potential of Ukraine needs stimulation of investment as a determining factor of progressive structural changes and pre-condition for the acceleration of progressive transformation in the structure of industrial production and upgrading production capacity. It has been proved that allocative management of development of industrial capacity is crucial for formation and generation of reproductive proportions inherent in structural and innovative model of development of the industry and national economy etc.
Challenges and Obstacles on the Way of Ensuring the Proceedings of Allocative Management of Development of Industrial Potential of Ukraine
Keywords: промисловий потенціал; алокаційне управління розвитком промислового потенціалу; industrial potential; allocative management of industrial potential development